Lease it or lose it? The implications of New York's Land Lease Initiative for public housing preservation. (January 2017) - Shamsuddin, Shomon; Vale, Lawrence J
Urban scholars frequently call for equitable and inclusive growth to create more just cities but this vision has proven elusive in urban development – especially involving low-income communities and affordable housing. In 2013, the New York City Housing Authority proposed to leverage private development to benefit low-income residents by supporting market-rate residential construction on open space in public housing sites to pay for needed improvements to subsidised units. The Land Lease Initiative was a seemingly win-win plan but quickly faced backlash from multiple quarters. Using interviews with key housing authority officials and analysis of plan documents and media coverage, we show how the content and framing of the plan stoked fears of displacement, despite stated intentions. Our analysis reveals that criticism overlooked four unconventional ideas for preserving public housing, which are embedded in the plan: (1) retaining all public housing units and high-rise public housing towers on site, as opposed to demolishing them; (2) deconcentrating poverty by increasing residential density, instead of displacing poor residents; (3) adding affordable housing units to the site of low-income public housing; and (4) creating mixed-income communities around buildings, in addition to within them. The findings suggest that the future of affordable housing in the neoliberal era involves blurring the line between preservation and privatisation.